Main Character™s Personality in a Movie the Lion King - Purba, Anita Purnama Sari Br; Gultom, Feriyanti Elina (TRANSFORM: Journal of English Language Teaching and Learning, 2023)
This research is a study that analyzes the personality traits of three main characters™ (simba, mufasa and scar) in the movie The Lion King . This study aims to determine the character and characterization of the main character in the lion king movie. This research is included in the literature study. The researcher focuses on dialogue and subtitle in the movie, and after that analyzes the characters and characterizations based on the theory of Paul Costa and Robert McCrae. There are five personality traits, namely extraversion, neuroticism, conscientiousness, openness to experience, and agreeableness. In this study, researchers found three of the Big Five Personality traits on the characters, Simba™s personality type are Extraversion And Neuroticism, Mufasa™s personality type are agreeableness and Neuroticism, and Scar™s personality type is Neuroticism .This study used a qualitative description method. The writer employs herself to collect the data by reading the subtitle, watching the film and marking them. From the analysis of the personality of the three main characters™ in the lion king movie, it can be concluded that the personality traits from The Big Five personalities are used in the film. From the theory used, the researcher found that the characteristics of Simba™s Extraversion are positive emotional, active and assertive And Neuroticism of simba are anxiety, self-consciousness, hostility and depression, Mufasas™ agreeableness are trusting, straightforward, altruistic and modest, Neuroticism of mufasa are anxiety and hostility, and Scar Neuroticism are vulnerability, impulsive, self-consciousness, hostility and depression.